Role of Imaging in Bariatric Surgery: A Review of the Various Surgical Techniques and Their Complications - Girishekar, Bhavana; Rawat, Sudarshan; Ananthasivan, Rupa; Reddy, Pramesh; Patil, Pooja; Kaushik, Kavya (Journal of Gastrointestinal and Abdominal Radiology, 2021)
According to the World Health Organization, obesity has reached epidemic proportions globally, with at least 2.8 million people dying each year as a result of being overweight or obese. Bariatric surgery is being increasingly used as a form of treatment, particularly in those patients where lifestyle modifications are deemed insufficient. With the role of radiologists transitioning from a medical to a surgical evaluation in obesity, it is becoming increasingly important to familiarize oneself with the various imaging techniques used in the preoperative and postsurgical evaluation in such cases. This article aims to review the various surgeries performed, their normal imaging appearance, and the various complications that could be encountered.
Keywords: bariatric surgery; gastric banding; obesity; roux-en-y gastric bypass; sleeve gastrectomy